Reagent Strips as an Aid to Diagnosis of Neonatal Meningitis in a Resource-limited Setting. (29th January 2018) - Burgoine, Kathy; Ikiror, Juliet; Naizuli, Ketty; Achom, Linda; Akol, Sylivia; Olupot-Olupot, Peter
Abstract: Background: Without early recognition and treatment, neonatal meningitis (NM) has a high mortality and morbidity. Although some neonates have features of NM, many do not. In many low-resource settings, the laboratory support to diagnose NM is not available, and bedside diagnostics are needed. Methods: This retrospective study was conducted in a neonatal unit in Uganda. Clear cerebrospinal fluid samples were routinely screened for glucose, protein and leukocytes on a Combur ® -10 urinalysis reagent strip. A definitive diagnosis was made using laboratory analysis. The results of the screening and definitive tests were compared. Results: The reagent strip showed moderate sensitivity and high specificity for leukocytes ≥10×10 6 cells/l, high sensitivity for protein ≥100 mg/dl and high specificity for glucose <50 mg/dl. Conclusion: The use of reagent strips has the potential to improve and hasten the diagnosis of probable NM in settings where adequate or timely laboratory support is not available.